IMPLEMENTASI PROGRAM BANTUAN BERAS MISKIN - Emilia Emharis (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Rice Poor Implementation Assistance Program. The aim in this study was to determine and analyze the implementation of poor rice aid program in Kuantan Singingi in 2013 (Case In Sub Pangean) and the factors that affect implementation. This research uses descriptive method, quantitative. The study population was Target Households (RTS) as many as 1,316 people, and sampled using Slovin formula, as many as 100 people, using probability sampling. And data analysis was performed through frequency tables with data reduction, panyajian data and draw conclusions. The results showed that the distribution of rice to the poor people are less precise and only 1 (one) a reliable indicator that the quality of rice delivered.